Strategies of Human Resources Development at Dr. (H.C.) Ir. Soekarno Public Hospital Bangka Belitung - Armayani Rusli; Alfitri Alfitri; Raniasa Putra (International Journal Labs, 2022)
Human resource development in the health sector can be directed to the development of professional, quality and competitive human resources. This study aims to analyze the strategy of developing human resources at the Regional General Hospital Dr. (H.C) Ir. Soekarno, Bangka Belitung Islands Province. The research method used is descriptive qualitative using Wernefelt's RBV theory. This research resulted in a Human Resource Development Strategy that has been carried out by the Regional General Hospital Dr. (H.C) Ir. Soekarno, Bangka Belitung Islands Province. Hospital institutions are responsible for improving the work ability, skills and work behavior of staff and employees for the better. Human resource development strategy is a form of appreciation from the leadership/management towards employees in the form of education and training. The development of human resources in superior service products that are competitive and competitive in advancing hospitals against competition in the province of the Bangka Belitung Islands.